2022
DOI: 10.3233/jad-215329
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Specific Patterns of Body Mass Index Relationship with White Matter Connectivity

Abstract: Background: Obesity is an increasingly recognized modifiable risk factor for Alzheimer’s disease (AD). Increased body mass index (BMI) is related to distinct changes in white matter (WM) fiber density and connectivity. Objective: We investigated whether sex differentially affects the relationship between BMI and WM structural connectivity. Methods: A cross-sectional sample of 231 cognitively normal participants were enrolled from the Knight Alzheimer Disease Research Center. Connectome analyses were done with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 105 publications
2
6
0
Order By: Relevance
“…Disrupted structural connectome in these fibers, notably in the fornix, AF, and IFOF have been noted with conversion to AD from mild cognitive impairment [56][57][58]58]. Similarly we have shown changes in the connectivity in these WM fibers with increasing BMI in healthy older adults [15]. These associational WM fibers connect the medial temporal lobe to other parts of the limbic system.…”
Section: Wm Tracts Related To Bmi and Conversion Inform Shared Pathop...supporting
confidence: 74%
See 2 more Smart Citations
“…Disrupted structural connectome in these fibers, notably in the fornix, AF, and IFOF have been noted with conversion to AD from mild cognitive impairment [56][57][58]58]. Similarly we have shown changes in the connectivity in these WM fibers with increasing BMI in healthy older adults [15]. These associational WM fibers connect the medial temporal lobe to other parts of the limbic system.…”
Section: Wm Tracts Related To Bmi and Conversion Inform Shared Pathop...supporting
confidence: 74%
“…Later work confirmed an independent relationship between obesity and white matter (WM) integrity in adults. Higher body-mass index (BMI), waist circumference or waist-to-hip ratio in mid-life adults is predictive of lower fractional anisotropy (FA) and decreased connectivity in the WM [9][10][11][12][13][14][15]. These mechanisms are shown to as least partly mediate the link between obesity and disrupted WM integrity and connectome through reduction of axonal density and demyelination [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Insulin resistance leads to changes in insulin signaling through the PBK/AKT and MAPK pathways, leading to metabolic effects and cell homeostasis [47]; changes in insulin resistance may contribute to the sustained chronic inflammatory response in the AD brain that facilitates neurofibrillary tangle development and β-amyloid plaques [48]. Obesity is common in both PCOS and T2D, and obesity is also associated with an increased risk of AD [49]. This, then, presents a complex milieu, with insulin resistance leading to increased obesity because of compensatory hyperinsulinemia [50]; however, conversely, obesity, through mechanisms of chronic inflammation, adipokine activation and mitochondrial dysfunction [18], leads to insulin resistance, so a vicious cycle may result.…”
Section: Discussionmentioning
confidence: 99%
“…Although prior studies have investigated the effects of VRFs on the architecture of the WM network [7][8][9][10] , most studies have focused on only a single VRF, and their results varied considerably due to small sample sizes and heterogeneity. For example, a recent study found no significant association between obesity and aging WM network architecture 11 , but Rahmani and colleagues identified gender-specific effects of increasing body mass index on WM network 12 . Therefore, large, homogeneous cohorts with comprehensive surveys are necessary to compare the effect sizes and the patterns of impairment caused by VRFs on the WM network, particularly with regards to gender-related effects.…”
Section: Introductionmentioning
confidence: 99%